Persepsi Mahasiswa Jurusan Sosial Ekonomi Fakultas Pertanian Universitas Sam Ratulangi Tentang E-Commerce Melalui Facebook - Sereh, Didit Saputra; Waney, Nordy Fritsgerald Lucky; Baroleh, Jenny (AGRI-SOSIOEKONOMI, 2023)
This study aims to describe students' perceptions of e-commerce through Facebook. The research was conducted at during to Juni 2023. The data collected is primary data obtained from direct interviews with student of the Department of Socio-Economics Faculty of Agriculture Sam Ratulangi University. Secondary data is obtained from journals, research reports taken from the internet. The data collected of the study were analyzed by descriptif. The results showed that the perceptions on the doubling of Facebook functions as social media into e-commerce facilities received good appreciation because it made it easier and helped save time, money and energy. Student’s perceptions of using Facebook e-commerce, namely buying and selling goods through Facebook e-commerce is very easy because the transaction method is the same as using Facebook in general, so they have almost no obstacles in carrying out e-commerce activities through Facebook. Students' perceptions of e-commerce services through Facebook are very good because in conducting e-commerce activities through Facebook, buyers and sellers always prioritize friendliness and courtesy when interacting in terms of bargaining activities.